(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Due to new circumstances of living, climate and environmental changes, varieties of human body shapes are growing. Therefore, obtaining uniformly clothes for special issues in the group of people with similar interests (dancing groups, choirs, etc.) are getting more and more complex. Besides the self-estimation and perception about the shape and size of the person varies due to different sizing from brand to brand. To dress-up the group of people with different sizes in uniformly way is not an easy task for the supplier – even if the model chosen for the gown is casual, most of the producers doesn’t apply a large scale of sizes. Frequently sizing systems do not fit to the needs of the end-users. Size marked on the clothing describes only some information about body size, if any. Therefore, part of clothing supplied is not suitable for end-user groups, but if already purchased it is decided to discard them. Such a set of circumstances, in contrast to global progress towards sustainable development, which is also based on environmental responsibility, can serve as a contributing factor to further growth in clothing consumption. The main purpose of this study is to make an insight into sizing approaches for a special group of people focusing on the best practice of human body 3D scanning. The paper outlines a certain target group’s understanding of the clothing size correspondence to their individual body characteristics. Advantages of human body scanning for analysing of body characteristics and solving sizing issues are discussed. Within the study, anthropometric data sets of 50 women group were obtained using a 3D scanner to develop the distribution of this special group into size groups and analyse individual body measurements that are significant for the design of appropriate garment patterns. Conclusions made in this paper acknowledge 3D scanning as an advantageous method for anthropometric data obtaining which are determinate for garment design and sizing system development.